Women, War and Memory: Exploring the Experience of the Algerian Women through the Lens of Fadilah Al-Faruq’s Tāʽul Khajal - Yakub Abdulwahab; Adams Akewula (آداب الكوفة)
This paper, titled Women, War and Memory in Fadilah Al-Faruq’s Tāʽul Khajal, explores how Al-Faruq’s narrative challenges conventional representations of war, gender, and memory of post-colonial Algeria. By examining the portrayal of rape and abduction within the novel, this study reveals how literature functions as both a mirror and a mediator of societal trauma, capturing the stigmatization of feminine bodies and the enduring scars left by war. In doing so, it highlights the indispensable role of literary expression in preserving the collective memory of postcolonial Algeria and in forging paths toward resistance and recovery. The paper argues that Al-Faruq uses innovative narrative form to weave together personal memory and collective trauma. The novel's haunting passages—such as the recollection of the "year of shame" in 1994, which witnessed the assassination of 151 women and the systematic abduction and rape that followed in 1995—illustrate how extreme violence was weaponized by groups like the GIA. Their public communiqués, declaring an expansion of their "battle" to include the women of those who opposed them, reduced female bodies to symbols of ideological purity and targets for brutal retribution. These narratives, filled with explicit details of These narratives, filled with explicit details of violence and loss, confront the reader with the unvarnished reality of gender-based violence and the pervasive silence that shrouds official accounts of these atrocities. By integrating these vivid accounts with theoretical insights on memory the novel underscores the dual role of trauma literature: it documents the psychological and social repercussions of violence while also challenging the structural norms that perpetuate gendered oppression. In doing so, al-Faruq’s work compels us to recognise that the violence inflicted during wartime cannot be disentangled from the everyday abuses rooted in patriarchal and colonial legacies.